A Comparison of Community and Clinic Baby Showers to Promote Safe Sleep for Populations at High Risk for Infant Mortality. (16th March 2016) - Ahlers-Schmidt, Carolyn R.; Schunn, Christy; Lopez, Venessa; Kraus, Stacey; Blackmon, Sheila; Dempsey, Millicent; Sollo, Natalie
Community baby showers have provided education and free portable cribs to promote safe sleep for high-risk infants. We evaluated knowledge gained at these showers and the effectiveness of holding baby showers at a primary care clinic as an alternative to traditional community venues. Participants at the community venue were more likely to exhibit risk factors associated with unsafe sleep and to report an unsafe sleep location for their infant without the provided portable crib. Following the showers, both groups showed improvement in knowledge and intentions regarding safe sleep. However, to connect with the highest risk groups, showers held at community venues appeared to be preferable to those held at high-risk clinics.